Analysis of serum reproductive hormones and ovarian genes in pubertal female goats - Yanyun Zhu; Jing Ye; Ping Qin; Xu Yan; Xinbao Gong; Xiaoqian Li; Ya Liu; Yunsheng Li; Tong Yu; Yunhai Zhang; Yinghui Ling; Juhua Wang; et al. (BMC, 2023)
Abstract Background Age at puberty is an important factor affecting goat fertility, with endocrine and genetic factors playing a crucial role in the onset of puberty. To better understand the relationship between endocrine and genetic factors and mechanisms underlying puberty onset in goats, reproductive hormone levels were analyzed by ELISA and ultraperformance liquid chromatography-multiple reaction monitoring-multistage/mass spectrometry and RNA sequencing was performed to analyze ovarian genes. Results Serum follicle stimulating hormone, luteinizing hormone, estradiol, 11-deoxycortisol, 11-deoxycorticosterone, corticosterone, cortisone, and cortisol levels were found to be higher but progesterone were lower in pubertal goats as compared to those in prepubertal goats (P < 0.05). A total of 18,139 genes were identified in cDNA libraries, and 75 differentially expressed genes (DEGs) were identified (|log2 fold change|≥ 1, P ≤ 0.05), of which 32 were significantly up- and 43 were down-regulated in pubertal goats. Gene ontology enrichment analyses indicated that DEGs were mainly involved in "metabolic process," "signaling," "reproduction," and "growth." Further, DEGs were significantly enriched in 91 Kyoto Encyclopedia of Genes and Genomes pathways, including estrogen signaling pathway, steroid hormone biosynthesis, and cAMP signaling pathway. Bioinformatics analysis showed that PRLR and THBS1 were highly expressed in pubertal ovaries, and ZP3, ZP4, and ASTL showed low expression, suggesting their involvement in follicular development and lutealization. Conclusions To summarize, serum hormone changes and ovarian DEGs expression were investigated in our study. Further studies are warranted to comprehensively explore the functions of DEGs in goat puberty.